Prognostic factors associated with recurrence in patients undergoing surgery for hepatic cystic echinococcosis: A systematic review protocol - Josue Rivadeneira; Luis Fuenmayor-González; Anis Hasnaoui; Diomaris Ortiz; Gabriela Zambrano; Claudio Rojas-Pincheira; Carlos Manterola (PLoS ONE, 2025)
Background Cystic echinococcosis (CE) is a zoonotic disease caused by Echinococcus granulosus, with hepatic localization being the most frequent presentation in humans (70–80%). Surgical intervention remains the most common therapeutic option, despite an associated recurrence rate of 8% (95% CI: 6%–10%). CE recurrence increases postoperative morbidity, hospital stay, and healthcare costs. Several prognostic factors (PFs), such as cyst size, presence of multiple cysts, and personal or family history of CE, have been linked to recurrence. However, associations with cyst location, type, and biliary complications remain uncertain due to conflicting evidence. This systematic review (SR) aims to identify PFs associated with recurrence in patients undergoing surgery for hepatic CE. Methods We will conduct a systematic review of primary longitudinal observational, and experimental studies evaluating the association between clinical, parasitic, and surgical PFs and CE recurrence. We will search Medline, Scopus, Embase, Web of Science, BIREME-BVS, and SciELO using a sensitive search strategy. Two reviewers will independently screen studies, extract data, and assess risk of bias using the QUIPS tool. Methodological quality will be assessed using MInCir-Pr2, and data extraction will follow the CHARMS-PF checklist. A qualitative synthesis will be performed, and where appropriate, random-effects meta-analyses will be conducted using the inverse-variance and restricted maximum likelihood methods. Heterogeneity will be assessed using Chi², Tau², I², and 95% prediction intervals. Publication bias will be explored via funnel plots and statistical tests (Egger’s). Certainty of evidence will be assessed using GRADE. Discussion The results of this SR will support early risk stratification and inform clinical decision-making in the management of hepatic CE, a neglected tropical disease. Registration PROSPERO, CRD42024538005.